An Analysis of the International Legal Framework for the Protection of Coral Reefs - Guy, Laura (Institute of Marine and Environmental Law, 2014)
The biodiversity found on a coral reef is above and beyond that found in the tropical rainforests, with an estimated 25 percent of all marine species concentrated in an area that only covers 1 percent of the ocean floor. This huge wealth of biodiversity is founded upon a structure made entirely of animals. The coral polyps that provide the limestone structure of the reef date back around 200 million years and they in that time, although their growth is slow, have produced huge areas of various types of reef. These include atolls, fringing reefs and barrier reefs, the most famous being that of the Great Barrier Reef in Australia which covers around 350,000 square kilometres.